Innovative biomass-driven pathways for green ammonia and urea production with integration of carbon capture - Erdemir, Dogan; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
Urea and ammonia are vital fertilizers traditionally produced via the fossil-fuel-intensive Haber-Bosch process, which accounts for significant global carbon dioxide emissions. Transitioning to green ammonia and urea production is essential for sustainable agriculture and meeting the climate goals through the integration of renewable energy and carbon capturing technologies. This study investigates the feasibility of a biomass-driven system to achieve carbon-neutral synthesis while addressing the challenge of significant elemental variability in biomass feedstocks. A thermodynamic analysis is performed on 86 different biomass sources to evaluate an integrated system comprising oxy-combustion power generation, carbon capture, ammonia synthesis, and urea production across two distinct operational modes: a self-sufficient mode, and an hybrid mode that uses external energy to utilize all remaining carbon dioxide. In self-sufficient mode, the system produces a constant 118.7 kg of urea per 1 MWh of electricity using a median of 4.8 tons of feedstock, while the hybrid mode utilizes remaining carbon to produce an additional 1.25 tons of urea at a massive energy cost of 16,100 kWh. The findings demonstrate that while the system is technically viable, its economic feasibility is critically dependent on securing off-peak electricity rates of approximately $0.039/kWh to bring production costs in line with global market benchmarks.
Keywords: Green urea; Green ammonia; Biomass; Carbon Capture and Utilization; System Integration; Energy analysis; Self-Sufficient System; TECHNOLOGIES; RECOVERY; WASTE; Thermodynamics; Energy & Fuels; Mechanics